2015
DOI: 10.3109/14767058.2015.1094788
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of multiple factors which may contribute to vitamin D levels of bedridden pregnant women and their preterm neonates

Abstract: Due to insufficient exposure to sunlight and a diet not enriched with vitamin D, bedridden pregnant women suffer from vitamin D deficiency and pregnancy complications lead often to birth of preterm neonates with the same deficiency. Mothers should increase the total amount of vitamin D intake (food and supplement).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…In the present study, the Pearson correlation coefficient for the serum level of vitamin D in mothers and infants shows a strong and significant relationship between the serum level of vitamin D in mothers and preterm infants. In this context, Skouroliakou et al reported a strong and significant correlation between the serum level of vitamin D in mothers and preterm infants, which confirms the results of the present study [ 20 ]. In the study of Mafinejad et al, a strong and significant relationship was demonstrated between serum levels of vitamin D in mothers and preterm infants, which is in line with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the Pearson correlation coefficient for the serum level of vitamin D in mothers and infants shows a strong and significant relationship between the serum level of vitamin D in mothers and preterm infants. In this context, Skouroliakou et al reported a strong and significant correlation between the serum level of vitamin D in mothers and preterm infants, which confirms the results of the present study [ 20 ]. In the study of Mafinejad et al, a strong and significant relationship was demonstrated between serum levels of vitamin D in mothers and preterm infants, which is in line with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In this field, in the study of Skouroliakou et al, the logistic regression model showed the effect of mothers’ serum vitamin D level in predicting the level of more than 20 ng/ml of vitamin D in preterm infants, which confirms the results of the present study [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
“…Unadjusted analysis of the association between clinical data and vitamin D levels in the CB that was conducted on 241 mother-infant pairs (72.6% black and 81.3% multiparous) revealed lower vitamin D levels in the cord blood of nulliparous women [31]. Comparable to previous reports we found no difference between the CB vitamin D status and maternal multivitamin supplementation [30, 32]. However, others have reported that the use of multivitamins, which usually include 400 IU vitamin D 3 , is associated with increased concentrations of 25(OH)D in CB [4].…”
Section: Discussionmentioning
confidence: 38%
“…In our neonatal unit, premature and HIV exposed newborns are supplemented with a multivitamin formula that consists of 400 IU of vitamin D (in each 0.6mls), other essential vitamins, and Omega 3 from fish oil. This is based on recommendations from the national guidelines [ 25 ].…”
Section: Discussionmentioning
confidence: 99%